Drug resistance gene amplification of plasmid NR1 derivatives with various amounts of resistance determinant DNA. - Peterson, B C (1985)
Drug resistance gene amplification of derivatives of plasmid NR1 having various amounts of resistance (r) determinant DNA was examined with two types of NR1 derivatives. The first was an NR1 derivative that carried two tandem copies of the r determinant component which was isolated as an intermediate in the amplification process. The plating efficiency of host cells and restriction endonuclease analysis of the plasmid DNA indicate that plasmids with two tandem copies of the r determinant undergo spontaneous amplification to a more highly amplified state at a frequency 150-fold higher than that of wild-type NR1. The second class of derivatives consisted of plasmids in which different regions of the r determinant component had been deleted. The relationship between spontaneous amplification frequency and r determinant size was examined with these plasmids. Plating efficiency of host cells indicated that plasmids with a smaller r determinant undergo spontaneous amplification at a lower frequency than do plasmids with a larger r determinant. These results suggest that there is an ordered sequence of events in the amplification of the r determinant of NR1.